The Impact of Rice Price Increase and Financial Distress Risk on Student Finance (A Cast Study of Management Student at Unismuh Makassar) - Nurhafizah, Nurhafizah; Abdi, Muhammad Nur; Nanda, Sahabuddin (Dinasti Publisher, 2025)
This study aims to examine the influence of rice price increases and financial distress risk on the financial management of Management Department students at Muhammadiyah University of Makassar. The population of this study consisted of 376 students from the 2021 cohort of the Management Department, Faculty of Economics and Business, Muhammadiyah University of Makassar. The sample size was determined using the Slovin formula, resulting in 79 respondents. This research employed a quantitative approach with data collected through questionnaires. The data were analyzed using multiple linear regression analysis with SPSS version 22. The results show that the rice price increase variable (X1) has a positive and significant effect on student finances (Y) with a regression coefficient of 0.470 and a significance value of 0.004. Similarly, the financial distress risk variable (X2) also has a positive and significant effect on student finances (Y) with a regression coefficient of 0.435 and a significance value of 0.010. Both independent variables explain 45.7% of the variation in the student finances variable, while the remaining 54.3% is influenced by factors not examined in this study.